Severe Cholestatic Syndrome Secondary to Graves’ Disease - da Silva, Rodrigo Piltcher; Morillos, Matheus Bernardon; Junior, Sabino Bertão; Miclos, Isabella Roque; Weinert, Letícia Schwerz; Marques, Rogério Torres (Clinical and Biomedical Research, 2019)
This paper reports a case of severe cholestasis as an atypical manifestation of Graves’ disease. It discusses the pathophysiology, the diagnosis and the investigation of this complication of hyperthyroidism as well as the impact of this finding on the therapeutic options for managing the disease. Keywords: Graves’ disease; hyperthyroidism; cholestasis